Segmental hemodynamics during partial liquid ventilation in isolated rat lungs - Ko, Angela C. (2003)
Partial liquid ventilation (PLV) is a means of ventilatory support in which gas ventilation is carried out in a lung partially filled with a perfluorocarbon liquid capable of supporting gas exchange. Recently, this technique has been proposed as an adjunctive therapy for cardiac arrest, during which PLV with cold perfluorocarbons might rapidly cool the intrathoracic contents and promote cerebral protective hypothermia while not interfering with gas exchange. A concern during such therapy will be the effect of PLV on pulmonary hemodynamics during very low blood flow conditions. In the current study, segmental (i.e. precapillary, capillary, and postcapillary) hemodynamics were studied in the rat lung using a standard isolated lung perfusion system at a flow rate of 6 ml/min ( ~5% normal cardiac output). Lungs received either gas ventilation or 5 or 10 ml/kg PLV. Segmental pressures and vascular resistances were determined, as was transcapillary fluid flux. The relationship between individual hemodynamic parameters and PLV dose was examined using linear regression, with n = 5 in each study group. PLV at both the 5 and 10 ml/kg dose produced no detectable changes in pulmonary blood flow or in transcapillary fluid flux (all R(2) values < 0.20). Conclusion: In an isolated perfused lung model of low flow conditions, normal segmental hemodynamic behavior was preserved during liquid ventilation. These data support further investigation of this technique as an adjunct to cardiopulmonary resuscitation.